(untitled) (Research, Society and Development, 2021)
The homeopathic treatment granted by the unique health system arrived in Brazil in 1840 and in 1980 it began to be offered in the public system, in the unique health system complementary and traditional medicine is used, where such practices involve homeopathy, acupuncture. The main objective is to present an analysis of homeopathic treatment in SUS, which today is recognized as a medical and pharmaceutical specialty that is a science based on the principles of similitude, pathogenic experimentation, dilution, and the single drug principle. It was conducted by means of a literature search, in an electronic search in the Lilacs, Scielo, and Pubmed databases. Among the inclusion criteria were included full texts, articles published in the last 7 years (2014 to 2021), in Portuguese language, in the electronic databases already informed. As a main result observed through the research conducted, there is still a scarcity of publications of articles and studies that address the homeopathic treatment offered by SUS. Still, the practice of care is of fundamental importance for the qualification of such actions, as well as in integral and significant health care to develop knowledge about the analysis and the possibility of seeking to understand more about the still little explored subject.